Lateral Ventricle to Sylvian Fissure Shunt for Obstructive Hydrocephalus: First Report - Patkar, Sushil (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Cerebrospinal fluid (CSF) pathway studies have revealed that the CSF secreted from the choroid plexus of the ventricles after egressing from the fourth ventricle reaches the basal suprasellar cistern and ultimately the sylvian cisterns. From the sylvian cistern, the CSF travels over the cerebral convexity subarachnoid space to reach the superior sagittal sinus and enters the bloodstream. Diverting CSF from the lateral ventricle with a shunt catheter to the sylvian cistern can be an option to treat obstructive hydrocephalus. An adult patient with posttraumatic hydrocephalus with contraindications to ventriculoperitoneal and ventriculoatrial shunt placement underwent this procedure of diverting CSF from the lateral ventricle to the sylvian cistern successfully, and he had immediate relief of symptoms of raised intracranial pressure. Although preliminary results seem logical and promising, more cases and longer follow-up is required to consider this shunt operation an option in the treatment of obstructive hydrocephalus.
Keywords: hydrocephalus; ventriculoperitoneal shunt; shunt complications; cerebrospinal fluid; overdrainage